The mediating effects of moral belief in predicting online moral engagement - Hussein, Eliza; Wok, Saodah (UPM Press, 2021)
The aim of this study is to investigate whether moral traits, moral identity, and moral belief affect online users’ moral engagement. Specifically, the objectives of the study are: (1) to determine the levels of moral traits, moral identity, moral belief, and online moral engagement; (2) to determine the relationships between moral traits, moral identity, moral belief, and online moral engagement; and (3) to investigate the mediating effect of moral belief on the relationships of moral traits and moral identity with online moral engagement. This study employed a quantitative research design using the online survey technique for data collection. A total of 153 respondents was collected. Results show high levels of moral traits, moral identity, moral belief, and online moral engagement exercised by the students. Moral belief partially mediated the relationships of moral traits and moral identity with online moral engagement. These findings support Mill’s harm principle that any kind of expression should be allowed but guided by self-restriction and not harm others. Therefore, the study suggests for a focus on moral nurturing among Malaysian youths to minimize the total freedom of expression of harmful information being disseminated unnecessarily especially online.